Empowering equality: How the right to information fuels inclusive development - Ranjan, Rajesh; Singh, Rashmi; Tripathi, Saumya (Edelweiss Applied Science and Technology, 2025)
The Right to Information (RTI), grounded in Article 19(1) of the Indian Constitution, is widely regarded as a fundamental human right—one that upholds the dignity of every individual. Often referred to simply as the RTI Act, it empowers citizens to demand transparency and accountability from public authorities. However, to truly harness the potential of this right, there needs to be a significant shift in mindset—not just among the public, but also within the government, bureaucracy, and political leadership. It’s essential to promote the understanding that the RTI is not a hurdle to governance, but rather a powerful tool for progress and growth. When embraced fully, the disclosure of information can foster trust, improve public service delivery, and strengthen democracy. This transformation in attitude can be achieved through widespread education, awareness campaigns, and training programs focused on the value of transparency. Historically, the media has played a vital role in spreading information, particularly during India’s struggle for independence against British rule. In today’s context, where India stands as the world’s largest democracy, the media’s responsibility has only grown. By raising awareness and keeping both the public and officials informed, the media can play a pivotal role in promoting RTI, leveling the playing field, and encouraging open, inclusive governance.